2021
DOI: 10.1186/s13717-021-00292-7
|View full text |Cite
|
Sign up to set email alerts
|

Ecological implications of twentieth century reforestation programs for the urban forests of São Paulo, Brazil: a study based on litterfall and nutrient cycling

Abstract: The focus of this study was to investigate the wide use of Eucalyptus spp., an exotic plant with high allelopathic ability, in the reforestation programs of urban parks in São Paulo City, Brazil, over the last century. To understand the implications of using Eucalyptus spp. in the city’s parks, this study aimed to compare nutrient cycling and litter decomposition between a mixed composition of litter (i.e., native and exotic species) and the litter of a single species (i.e., Eucalyptus). To accomplish this, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…G N represents the annual absorption of nitrogen oxides by the evaluated forest, and K N represents the cost of fluoride treatment. The calculation for the value of dust retention is shown in Equation (10) [34].…”
Section: Construction Of Evaluation Index System For Urban Forest Eco...mentioning
confidence: 99%
See 2 more Smart Citations
“…G N represents the annual absorption of nitrogen oxides by the evaluated forest, and K N represents the cost of fluoride treatment. The calculation for the value of dust retention is shown in Equation (10) [34].…”
Section: Construction Of Evaluation Index System For Urban Forest Eco...mentioning
confidence: 99%
“…U z = U TSP + U PM10 + U PM2.5 (10) In Equation (10), U TSP represents the value of the annual overdue TSP of the evaluated forest stand. U PM10 represents the value of annual late payment PM10 in the assessed forest stand.…”
Section: Construction Of Evaluation Index System For Urban Forest Eco...mentioning
confidence: 99%
See 1 more Smart Citation
“…Leveau ( 2021 ) found that environmental filtering by urbanization led to phylogenetical randomness and functional clustering of bird communities in urban habitats. By comparing nutrient cycling and litter decomposition between the litter of a single species and a mixed composition of litter in urban parks in São Paulo City, Brazil, Ferreira et al ( 2021 ) found that both environmental and biogeographic characteristics of the species shall be considered in urban reforestation programs. Additionally, Liu et al ( 2021 ) found that spatial processes and environmental filtering equally contributed to macroinvertebrate metacommunity dynamics in the highly urbanized subtropical river networks in Shenzhen, South China through examining ecological factors and the seasonal difference in structuring macroinvertebrates metacommunity.…”
Section: Linking Landscape and Environmental Changes To Ecological Pr...mentioning
confidence: 99%
“…As the urbanization process increases in cities, the exploitation of natural resources, the alteration of ecological patterns and processes and the reduction of green areas have become an important focus of study (Ferreira et al, 2021;Pereira et al, 2022;Ramon et al, 2022). Urban green areas accomplish important functions such as oxygen production, adjusting the microclimate, and absorbing pollutants, in addition to its landscape function (Silva & Vargas, 2010).…”
Section: Introductionmentioning
confidence: 99%